2008
DOI: 10.1002/app.28746
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of morphologically different, metal absorbing aniline‐formaldehyde polymers including micron‐sized sphere using simple alcohols as morphology modifier

Abstract: Aniline-formaldehyde condensate (AFC) is an amine functional group containing polymer. The sticky resinous nature of the polymer limits its usefulness. Synthesis of AFC in presence of methanol, isopropanol, t-butanol, n-octanol or glycerine formed solid cakes instead of resinous material. The scanning electron microscopic (SEM) picture of the polymer synthesized in presence of t-butanol shows the formation of micron sized spheroids while the presence of methanol, isopropanol, n-octanol and glycerine leads to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The bands at 1512 cm -1 and 821 cm -1 can be assigned to the stretching vibration of benzenoid framework and the bending vibration of substituted benzene ring, respectively. The absorption bands at 1615 cm -1 and 1267 cm -1 are assigned to -NH and -C-N-stretching vibrations, respectively, while the characteristic band observed at 3345 cm -1 indicates that the copolymers contain primary and/or secondary amine functional groups [32,35,40,41]. However, changes in the IR spectra of as-synthesized copolymers occurred with a decrease in the molar ratio of aniline to formaldehyde.…”
Section: Molecular Structure Of Aniline-formaldehyde Copolymersmentioning
confidence: 84%
See 2 more Smart Citations
“…The bands at 1512 cm -1 and 821 cm -1 can be assigned to the stretching vibration of benzenoid framework and the bending vibration of substituted benzene ring, respectively. The absorption bands at 1615 cm -1 and 1267 cm -1 are assigned to -NH and -C-N-stretching vibrations, respectively, while the characteristic band observed at 3345 cm -1 indicates that the copolymers contain primary and/or secondary amine functional groups [32,35,40,41]. However, changes in the IR spectra of as-synthesized copolymers occurred with a decrease in the molar ratio of aniline to formaldehyde.…”
Section: Molecular Structure Of Aniline-formaldehyde Copolymersmentioning
confidence: 84%
“…Condensation polymerization of aniline and formaldehyde involves electrophilic addition of protonated formaldehyde to the ortho-and/or para-position of aniline depending on the ratios of aniline to formaldehyde [34,35]. The linear or cross-linked structure of the resultant polymer depends on the reaction stoichiometry, pH and temperature.…”
Section: Molecular Structure Of Aniline-formaldehyde Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of -CH 2 -linkages in the aniline-formaldehyde resin can be determined with the polymerization of aniline formaldehyde conducted under the acidic condition. Since any spherical texture in the composites prepared in this study was not observed, it can be concluded that the -CH 2 -linkage plays a main role in the aniline sphere formation [20]. The extent of crystalline character depends on the acidic nature of the monomers [21].…”
Section: Xrd and Sem Analysismentioning
confidence: 69%
“…The addition of formaldehyde to aniline in acidic medium forms a rubbery thermoplastic resin spontaneously, which is known as aniline formaldehyde condensate (AFC). It is extremely used in adhesive industry and also useful to bind Cr(VI) effectively in acid medium (74). AFC is effective even at low concentration of Cr(VI) (9 mg. L −1 ) and reduces Cr(VI) level by 70% at pH 3 (74).…”
Section: Polyamines and Polyanilinesmentioning
confidence: 99%